Manajemen Peserta Didik Untuk Meningkatkan Mutu Pendidikan - PALAH (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2020)
Judging from its effectiveness as an educational institution, educational problems often arise due to inappropriate management. The purpose of this study is to describe the management of students in the SMP Islam Terpadu Al-Firdaus Sukaraja Sukabumi. The research method used is literature review and small scale research, data collection is done through interviews, observations, and documentation studies. The results of this study show that (1) Student management includes; analysis of students' needs, recruitment of new students, selection of new students, orientation of new students, placement of new students, grouping of students, student discipline, and guidance and counseling services for students. (2) The management of students is carried out directly by the leaders of the pesantren, principals and vice-principals who are responsible for the program. Steps in implementing student management include disciplining students in following various programmed activities. (3) Student Management Evaluation is carried out through academic and non-academic assessments.